Un’analisi strutturale: Il corvo bianco di P. Bigongiari (ENTHYMEMA, 2011)
In this article we propose a structural analysis of the poem Il corvo bianco by Piero Bigongiari. We will highlight both the different textual layers and its intra- and inter-textual relationships. Moreover, by providing a survey of the compositional aspects of the poem, we will finally offer an overall symbolic interpretation.